2020
DOI: 10.1111/sifp.12110
|View full text |Cite
|
Sign up to set email alerts
|

Family Planning During and After the West African Ebola Crisis

Abstract: The West African Ebola outbreak of 2013–2016 had the potential to devastate family planning programs in affected countries, which had made great progress in years prior. We examine monthly provision of family planning service statistics from government sources for Liberia and Sierra Leone from 6 months before the first Ebola case to 24 months after the last Ebola case to measure the impact during and after the epidemic. By calculating the couple‐years of protection from service statistics, we find that family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 11 publications
(20 reference statements)
2
75
0
3
Order By: Relevance
“…The rise in first trimester TOP services in Tshwane and Ekurhuleni districts during the lockdown and onwards need critical attention especially in line with the unmet needs for contraception. Sharp declines in family planning visits and contraceptive use were also reported in Liberia, Sierra Leone and Guinea during the Ebola outbreaks and six months after the epidemic, (10,11) suggesting that the epidemic had sustained negative effects on reproductive health.…”
Section: Discussionmentioning
confidence: 96%
“…The rise in first trimester TOP services in Tshwane and Ekurhuleni districts during the lockdown and onwards need critical attention especially in line with the unmet needs for contraception. Sharp declines in family planning visits and contraceptive use were also reported in Liberia, Sierra Leone and Guinea during the Ebola outbreaks and six months after the epidemic, (10,11) suggesting that the epidemic had sustained negative effects on reproductive health.…”
Section: Discussionmentioning
confidence: 96%
“…A model calculation for 132 low- and middle-income countries showed that a deterioration in the two areas mentioned by only 10% within 1 year will lead to more than 15 million additional unintended pregnancies and more than 3 million additional unsafe abortions, with more than 1000 additional maternal deaths (Riley et al, 2020 ). From the experience with the Ebola epidemic in West Africa (Bietsch, Williamson, & Reeves, 2020 ; Camara et al, 2017 ; Sochas, Channon, & Nam, 2017 ), it can be concluded that the reproductive healthcare problems caused by the COVID-19 pandemic in low- and middle-income countries will be serious and long term.…”
Section: Covid-19 Effects On Sexual and Reproductive Health Issues Inmentioning
confidence: 99%
“…The unfortunate byproduct of this shift is the de-prioritization of other essential health care services such as access to contraception. The consequence of limited access to contraception is evidenced by historic and current data [18][19][20][21]. Research conducted by the United Nations sexual and reproductive health agency (UNFPA) projects that more than 47 million women could lose access to contraception leading to 7 million unintended pregnancies as a result of the COVID-19 crisis [22].…”
Section: Globalmentioning
confidence: 99%
“…Data from the Ebola virus outbreak in Western Africa shows service disruption in maternal and newborn care contributed to an estimated 3600 maternal deaths, neonatal deaths, and stillbirths. This is nearly equal to the number of deaths caused by the Ebola virus itself [ 21 ]. Disruption in contraception access also results in an increase in unsafe abortions, miscarriage, pregnancy complications, transmission of HIV and other sexually transmitted infections, as well as increased incidence of post-traumatic stress disorder, depression, suicide, and intimate partner violence [ 18 , 21 , 22 ].…”
Section: Scope Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation